The interaction of institutional quality and human capital in shaping the dynamics of capital structure in Viet Nam - Enrico Santarelli; Hien Thu Tran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The aim of this paper is to find which of two theories of capital structure - trade-off theory or pecking order theory - best explains the capital structure decision of non-state firms during the post-transition process in Viet Nam. We also investigate the effect of human capital, institutional quality, and their interaction on the capital structure decision. For empirical evidence, we use a unique database provided by the CIEM-DANIDA project covering around 2,000 micro, small, and medium-sized enterprises in Viet Nam for each year from 2003 to 2014. We estimate our empirical models by employing the System Generalized Method of Moments estimator. Our findings suggest that the capital structure of Vietnamese firms is a balance between the trade-off theory and the pecking order theory. On one hand, accessing formal debts is extremely tough for young and non-state firms; they bootstrap themselves out of financial constraints by stretching and making the most of their internal resources and assets. On the other hand, those with access to formal sources take advantage of leverage tools from using formal loans to exploit the tax benefits against the costs of financial distress. Other noteworthy findings include: (i) profitability and debt tax shields are no longer significantly important when entrepreneurs adopt informal debt financing; (ii) high-quality institutions with transparent and fair credit rationing rules will enable firms to reduce their reliance on debt financing; and (iii) while human capital encourages entrepreneurs to obtain more loans, its interaction with institutional quality deters debt financing and favours other financial sources.
Keywords: C23; D22; E41; G32; M21; 330; capital structure; trade-off theory; pecking order theory; formal/informal debt; institutional quality; non-state firms; Viet Nam